VITRECTOMY FOR PHACOANAPHYLACTIC GLAUCOMA SECONDARY TO POSTERIOR CAPSULAR RUPTURE IN AN ADULT WITH PERSISTENT HYPERPLASTIC PRIMARY VITREOUS. Issue Volume 12:Issues 2(2018) (2018) - Brennan, Nicholas; Petrou, Petros; Reekie, Ian; Pasu, Saruban; Kinsella, Matthew; Da Cruz, Lyndon
Abstract : Purpose: Persistent hyperplastic primary vitreous (PHPV) is a developmental anomaly in which the normal regression of the primary vitreous and hyaloid vasculature does not occur. In the literature, there are a few cases of PHPV in adulthood. We report the novel presentation of phacoanaphylactic glaucoma secondary to posterior capsular rupture in an adult with PHPV. We discuss the best management of this condition with a review of the literature on this topic. Methods: Case report and literature review. Results: Medical management was unsuccessful in this case and vitrectomy and fragmatome lensectomy improved vision from PL to counting fingers. Conclusion: This case is unusual in the age of the patient in question as PHPV usually presents in childhood, as such there are few accounts in the literature to guide optimum management of adult PHPV. We suggest that surgical management of late-presenting PHPV should be considered to improve functional outcome. Abstract : Persistent hyperplastic primary vitreous (PHPV) is a developmental anomaly in which the regression of the primary vitreous and hyaloid vasculature fails. There are few reported cases of PHPV in adulthood. The authors report the presentation and management of phacoanaphylactic glaucoma secondary to posterior capsular rupture in an adult with PHPV.